Lawfare y populismo punitivo: las dos caras en América Latina - Sáenz-Solís, Jesús (2023)
Justice systems in Latin America have undergone a series of transformations in recent years. This has implied a greater protagonism of judges in decisions, with a high impact on the political system. In this context, two phenomena have emerged: lawfare and punitive populism. Lawfare represents the arbitrary application of judicial means for the elimination and annulment of political adversaries. This phenomenon in Latin America has mainly had an impact on progressive sectors, which have been censured for promoting a series of reforms that modify the social and economic structure of the region. On the other hand, punitive populism is a trend that proposes the use of judicial tools in the penitentiary system, promoting "iron fist" policies in order to obtain political gain. These have mainly generated a weakening of procedural guarantees at the regional level and the criminalization of the most vulnerable sectors. This article argues that both phenomena have deep cultural and political roots, and that they are part of a single articulated continuum which it proposes to call the punitivist moment. This article argues that both phenomena have deep cultural and political roots, and that they are part of a single articulated continuum which it proposes to call the punitivist moment. This concept intends to demonstrate the relationship between the issues raised and how the conditions of exclusion and repression have deepened through the judicial systems, targeting two sectors: the poorest and those who defend them.